UNCERTAINTY IN PREDICTING THE FISH‐RESPONSE TO TWO‐DIMENSIONAL HABITAT MODELING USING FIELD DATA. (30th August 2012) - Boavida, I.; Santos, J. M.; Katopodis, C.; Ferreira, M. T.; Pinheiro, A.
ABSTRACT Both water managers and researchers have the same goal when it comes to fish conservation, namely, to sustain, to improve or to restore aquatic habitat. To this aim, two‐dimensional (2D) hydrodynamic models have been widely used in aquatic habitat studies because they simulate flow with high accuracy and can predict habitat dynamics. The River2D model is able to integrate the habitat suitability curves for fish life stages with the simulated depth and velocity fields and the riverbed characteristics of substrate and cover, thereby estimating the corresponding weighted usable area, and thus predicting the potential distribution of fish species in the river. However, little is known about the in situ variability associated with such predictions both for hydraulic and biological data, whereas ecological responses are known to be driven by variability. Moreover, when calculating habitat availability, differences can be found by considering in the weighted usable area formulation substrate or cover or even both. To test the level of predictive accuracy of hydraulic and biological simulations, we modelled the habitat use by two fish species, the Iberian barbel Luciobarbus bocagei and the Iberian straight‐mouth nase Pseudochondrostoma polylepis, according to their requirements for depth, velocity, substrate and cover and then compared measured and simulated hydraulic and biological outcomes using the River2D model. Results indicate that 2D simulation depends on data collection, especially the density and location of bed topography points. Substantial differences were found in the biological responses. Results may differ when choosing different habitat availability variables. Similarly, habitat use may also be influenced by other biotic and abiotic interactions occurring in ecosystems, and restoration planning should be aware of such variability. Copyright © 2012 John Wiley & Sons, Ltd.